Atmospheric electricity coupling between earthquake regions and the ionosphere - Harrison, R; Aplin, K; Rycroft, M (2010)
We propose a mechanism to explain suggested links between seismic activity and ionospheric changes detected overhead. Specifically, we explain changes in the natural extremely low-frequency (ELF) radio noise recently observed in the topside ionosphere aboard the DEMETER satellite at night, before major earthquakes. Our mechanism utilises increased electrical conductivity of surface layer air before a major earthquake, which reduces the surface-ionosphere electrical resistance. This increases the vertical fair weather current, and (to maintain continuity of electron flow) lowers the ionosphere. Magnitudes of crucial parameters are estimated and found to be consistent with observations. Natural variability in ionospheric and atmospheric electrical properties is evaluated, and may be overcome using a hybrid detection approach. Suggested experiments to investigate the mechanism involve measuring the cut-off frequency of ELF "tweeks", the amplitude and phase of very low frequency radio waves in the Earth-ionosphere waveguide, or medium frequency radar, incoherent scatter or rocket studies of the lower ionospheric electron density. © 2009 Elsevier Ltd.